Legislative Aspects of Road Safety in the Local Environment: Cooperation with the Company Intermatic, d.o.o. - Samogy, Laura; Koritnik, Boštjan (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
Road safety is a complex, multi-layered field based on the interaction between humans, vehicles, infrastructure, and the environment. Modern approaches are shifting from reactive accident analysis toward data-driven and proactive models that enable risk prediction and improved traffic safety. Digital technologies such as artificial intelligence, intelligent transport systems, and connected infrastructure play a key role by enabling more efficient traffic management and real-time decision-making. The European Union, through the “Vision Zero” strategy and the “Safe System” approach, aims to eliminate road fatalities by improving infrastructure, vehicle safety, and road user behavior. The regulatory framework consists of EU regulations, directives, and national legislation, which together govern traffic safety, enforcement, and data usage. A major emphasis is also placed on personal data protection (GDPR and national legislation), as modern traffic systems rely heavily on data collection and processing. At the local level, municipalities and enforcement bodies play a crucial role in traffic calming, speed control, and protecting vulnerable road users. Overall, road safety is increasingly addressed through an integrated approach combining legislation, technology, and preventive measures to reduce accidents and improve overall mobility safety.